Confronting Peace
XXIX, 386 p. 12 illus.
Keywords: Most recent works about the efforts of local communities caught up in a civil war have focused on their efforts to maintain security and safety from the violence that surrounds them. This book, in contrast, focuses on how local peacebuilding actors face new challenges and opportunities once a peace agreement has been signed at the national level. How local communities have coped with the demands of “peace” is the theme that runs through each chapter, written by authors with direct experience of grassroots communities struggling with such “problems of peace." Susan H. Allen is Associate Professor and Director of the Center for Peacemaking Practice at the Jimmy and Rosalynn Carter School for Peace and Conflict Resolution at George Mason University, USA. Landon Hancock is Professor at Kent State University’s School of Peace and Conflict Studies, USA. Christopher Mitchell is Emeritus Professor of Conflict Research atGeorge Mason University’s Carter School, USA. Cécile Mouly is Research Professor and Coordinator of the research group in Peace and Conflict at FLACSO Ecuador.